Injil Menurut Ulangan 6 - Sihombing, Aeron Frior; Hia, Oferlin; Ambopai, Aldi Feron Ando (Sekolah Tinggi Teologi Sriwijaya, 2024)
The Old Testament is the word of God, the statutes and laws of God, specifically in this writing is Deuteronomy 6. The research question is how is the gospel in Deuteronomy 6? This is also the purpose of this study, which is to explain the gospel or good news according to Deuteronomy 6. Editorial criticism is done by looking at the theology or ideology of the editor or writer. Through this, an interpretation of the text will be made. A redaction of the Deuteronomy 6 text will be made to look at the editor's inserts or additions. This type of research is biblical by using redaction criticism. God's statutes or laws are God's grace given to His people. It is a manifestation of God's fellowship with His people.